New approach to four-phase transmission systems: analysis of the transient response and the possible voltage surges - Kurokawa, S. [UNESP]; Costa, E. C. M.; Brandt, I. S. [UNESP]; Pissolato, J. (Inst Engineering Technology-iet, 2012)
This study describes a technical analysis of a four-phase line as a transmission system alternative. An analysis in the frequency and the time domains is performed to evaluate the electrical characteristics and the transient response of a generic four-phase system compared with those of a conventional three-phase transmission system. The technical features of this non-conventional system are discussed and reviewed based on the current literature. Thus, a new analysis of the four-phase system is presented that emphasises several technical characteristics that have not been discussed in previous studies.